Hadega Almnadmh and the way Almnasmh Abu Hassan Ali bin Muhammad Al-Haddad (( After 1040 e )) Chapter four: Regarding the demand for sustenance from news and poetry study and achieve - Majid wadi, Rashid Ahmed; Hussein, Ibrahim Saleh; Fayyad, Muhammad Taha (Journal of Tikrit University for Humanities, 2023)
The study deals with the fourth Chapter Regarding the demand for sustenance from news and poetry. The author opened this chapter with an honorable prophetic hadith. After which he gave verses to the poet in this sense. And a ruling on the companions and their followers. After stories about sustenance does not leave the place of time and seal this with a bug that asks for a friend. Even if it is at the farthest point of the home of sustenance.